The 'serial callers' of Ghana: how 'serial callers' influence public debate on talk radio and the implications for Ghana's public sphere - Nunoo, Favour E (My University, 2016)
The aim of this research is to investigate the ‘serial caller’ phenomenon in Ghanaian talk radio, by examining how serial callers influence the dynamics of public debate and the implications this has for Ghana’s public sphere. It traces the history and development of serial callers who muddy the waters of a clean clear debate on talk radio. The study finds that in Ghana, the discovery of radio as a political voice became an incentive for the systematization of ‘serial calling’. With serial callers operating as “hired guns”, their entry into public debate was to announce a scandal or a repetition of a scandal, to take turf in the debate for the political party that has hired them. The study also found that ‘hijacking’ and ‘skewing’ constituted some of the modes, forms and strategies of interaction serial callers adopted to intervene in the dynamics of the debate and frame the agenda for public discussion. It found also that some media decision‐makers in Ghana facilitated the entry of serial callers into the debate in order to attract greater participation of audience and to satisfy advertisers; in doing so, they neglected the professional ethical codes and standards. The study concludes by arguing that, the normative ideals of the public sphere in rational discussion do not apply on Ghanaian talk radio as the discourse is not rich in scope and depth, while also resulting in a politically polarized public sphere.
A research report submitted in partial fulfilment of the requirements for the degree of the University of Witwatersrand’s Masters by Coursework and Research Report in Journalism studies. Johannesburg, March 2015